Impact of adherence to treatment with tiotropium and fluticasone propionate/salmeterol in chronic obstructive pulmonary diseases patients. (July 2014) - Ismaila, A.; Corriveau, D.; Vaillancourt, J.; Parsons, D.; Dalal, A.; Su, Z.; Sampalis, J.S.
Abstract Objective: Poor adherence to treatment may contribute to the treatment gap in chronic obstructive pulmonary diseases (COPD). The aim of the current study was to describe the association between adherence to treatment and the risk of COPD moderate (ME) and severe (SE) exacerbations, and health care utilization. Research design and methods: Observational single cohort study utilizing the Quebec Provincial Health Insurance databases. All patients older than 40 years with a diagnosis of COPD between 2001 and 2010 were entered in the study cohort at the time of their first prescription for tiotropium (TIO) alone or co-administered with fluticasone propionate/salmeterol (TIO + FSC). Follow-up continued to the last known claim or death. Adherence was measured by the medication possession ratio (MPR) ≥80% and persistence defined as no treatment gap ≥30 days. Main outcome measures: ME was defined as use of an oral corticosteroid or antibiotic, SE as COPD related hospitalization or an emergency room (ER) visit. COPD related health care resource utilization ascertained was prescription of rescue medications, ER visits, hospitalizations, intensive care unit (ICU) admissions, intubations, and general practitioner (GP) and respirologist visits. Results: There were 23, 707 patients included in this study. Compliance and persistence with TIO for monotherapy patients were 61.1% and 47.6% respectively. For patients treated with TIO + FSC, compliance and persistence for TIO were 62.9% and 45.3% respectively, and for FSC they were 35.4% and 33.0%. Multivariate analyses showed a significant (P < 0.001) adjusted odds ratios for ME (ORME) and SE (ORSE) for TIO compliant vs. non-compliant patients (TIO: ORME = 0.543, ORSE = 0.712; TIO + FSC: ORME = 0.436, ORSE = 0.570). Similarly for FSC compliance: ORME = 0.546; ORSE = 0.749. Similar results were observed for persistence. Compliance and persistence with TIO and FSC were associated with significantly reduced rates of health care utilization. Conclusions: Despite the typical limitations of an administrative database study, the results of this large population-based study have shown that reduced adherence to treatment with TIO and FSC is associated with increased risk for exacerbations and higher health care utilization in COPD patients.